Chapter Lik "jake žene" u srpskoj prozi prve polovine XX veka - Mitrović, Marija (Biblioteca di Studi Slavistici, 2018)
A series of female characters living in small provincial centres, aware of their beauty and spirit, are present in the Serbian prose of the first half of the 20th century to a degree that might be striking to the contemporary reader. This paper examine the social, historical, anthropological and psychological characteristics of the leading female characters created by Stevan Sremac (Zona Zamfirova, 1903), Svetozar Ćorović (Majčina sultanija, 1906), Borisav Stanković (Nečista krv, 1910), Ivo Andrić (Anikina vremena, 1931).